Trabalho e conhecimento: aprendizado de trabalhadores ambulantes - Justo, Hirã Soares (Universidade do Vale do Rio dos Sinos, 2019)
The thematic of this thesis is part of the collective research effort of the Pedagogical Mediation and Citizenship research group of the Graduate Program in Education of the University of Vale dos Sinos (Unisinos). The main objective of this research is to contribute to the study of learning for work in capitalist social formation and its dialectic relationship with the construction of knowledge, especially through the study of the learning of the associated autonomous workers, located in the central square of the city of Alvorada , located in the State of Rio Grande do Sul, in the metropolitan region of Porto Alegre. Hegel, Marx, Engels, Vigotski, Mark Rosental, Prado Junior, Paulo Freire, Leôncio Basbaum, and David Harvey were the theoretical foundations that support this research that is based on dialectical materialism. The research achieves its purpose, as it materializes the systematization of some life experiences and work of these workers. At the same time, it collaborates in the construction of the theoretical field of Knowledge Theory and proposes another model of graphic representation of the Dialectic of Knowledge, problematizing and incorporating new theoretical categories. It is concluded that the Central Square workers learn mediated by the world in the struggle for existence, plunged into profound contradictions in the exclusionary context of the capitalist market. In the midst of the historical conditions of their time, considering the life trajectory of each worker, the challenge lies in a conscious and imperative action that enhances the praxis of learning in relation to multiple determinations. However, the workers participating in the research, so far, have not become aware of, nor have taken actions to overcome these limitations.
Keywords: Trabalhadores Ambulantes; Dialética do Conhecimento; Aprendizado; Street Vendors; Dialectic of Knowledge; Learning; ACCNPQ::Ciências Humanas::Educação